Platinum Thin Film Consisting of Well-Aligned Nanowires and Its Optical Behavior - Suzuki, Takashi; Miyata, Hirokatsu; Noma, Takashi; Kuroda, Kazuyuki (Journal of physical chemistry. C, 2008)
A nanostructured film composed of interconnecting aligned platinum nanowires is prepared by electrodeposition using a hard template of mesoporous silica film with uniaxially aligned mesochannels formed on a conductive substrate. Platinum is introduced into the mesopores through micropores, connecting adjacent mesopores, without influencing the mesoporous structure. The alignment of the nanowires is retained to some extent after the removal of the silica template, leading to the formation of a film with aligned platinum nanowires, although the structural regularity is largely degraded. Irrespective of the presence of the silica template, the obtained films show distinct macroscopic optical anisotropy in the visible region, reflecting the anisotropic localized surface plasmon resonance arising from individual nanowire, despite its interconnected structure. The aligned structure enables the observation of such an axis-dependent optical property in a macroscopic scale. This versatile replication method can be extended to the preparation of aligned nanowire assemblies with various compositions.